Dividend policy prior and after the NASDAQ bubble: An Empirical Investigation of 188 firms in the S&P Index - Yukun, Yao (2010)
Abstract This dissertation aims to investigate the dividend payments before and after the NASDAQ internet bubble of a sample of 188 listed firms on the S&P 500 index in the USA from 1995 to 2005. Because most firms reduce dividend payment in distress period as prior researches suggested, this dissertation focuses on exploring the factors that influence the probability of dividend reduction decisions from 2000 to 2005. A liner probability model is undertaken. Several potential factors that affect the firms’ decision to cut dividend are chosen: earnings, profitability, investment opportunity, binding debt covenant and firm size. Most results are consistent with prior empirical evidence except that firm size is found to have the mixing results relating to firms’ decision to cut dividends.